Export boosting policies and firm behaviour: Review of empirical evidence around the world - Stjepan Srhoj; Vanja Vitezic; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2020)
How effective are direct government policies for boosting exports? We answer this question with a structured overview of 34 studies covering 26 countries around the world, and in doing so, we provide nine findings. We show export boosting policies are heterogenenous by design and include export promotion policies, public grants for exporters, public export guarantee schemes, subsidised export loans, and randomised foreign market access programmes. Our review provides insights into policy effectiveness with respect to extensive and intensive export margins as well as firms' production function inputs and its outputs. Heterogeneity of effects across firm characteristics is emphasised and the discussion is enriched with new evidence on spillover effects from export boosting policies. Finally, we provide back-of-the-envelope calculations of aggregate macroeconomic effects and give recommendations for policymakers. Our findings show export boosting policies are relevant and proven-to-be-effective policy instruments.
Keywords: F13; F14; L15; L25; O10; O24; 330; export promotion policies; guarantees; grants; loans; impact evaluation; review